Majhni stroji za sečnjo - Košir, Boštjan (Gozdarski vestnik, 2005)
The article presents some typical characteristics of small harvesters, such asmachine weight, engine power (kW), dimensions and transmission of power and pulling forces. The favourable and negative features of such machines are described. The efficiency of small harvesters is presented in comparison with large machines, specifically considering early thinning, where the use of small machines would be most suitable. Apart from the small and the large harvesters there is also the group of medium size harvesters with a weight between 10 in 14t. The coefficients for the average distance between trees androute width have been calculated, which are required for a machine of a certain width. This was the basis for the definition of the machine's working range.
Keywords: redčenje; stroji; strojna sečnja